Functional and metabolic activity of blood neutrophilic granulocytes in children with erosive and ulcerative lesions of the stomach and duodenum with detected Helicobacter pylori infection - I. S. Litvinova; O. A. Kolenchukova (Медицинская иммунология, 2023)
The Helicobacter pylori bacterium is currently considered one of the leading etiopathogenetic factors in the formation of gastric and duodenal ulcer in children and adults. Despite many studies in this area, the mechanisms of phagocytic activity in response to exposure to Helicobacter pylori are not completely clear. The aim of the work was to obtain results on the functional and metabolic activity of blood neutrophilic granulocytes in children with Helicobacter pylori-associated erosive and ulcerative lesions of the stomach and duodenum. The object of the study are neutrophilic granulocytes isolated from the blood of patients and the control group. Samples were taken from 46 persons with Helicobacter pylori-associated erosive – ulcerative lesions of the stomach and duodenum aged 11 to 18 years and the control group, which consisted of 55 practically healthy persons who had this disease excluded in the same age range. A comparative analysis of the functional activity of cells using chemiluminescent analysis and metabolic activity by the bioluminescent method was carried out. Luminol was used as a chemiluminescence activator. The measurement of the functional activity of phagocytes was based on the determination of the base activity (spontaneous reaction) and the reserve capacity of the cells when they were exposed to the nonspecific inducer zymosan. There is a reduced activation index of neutrophils in patients relative to the control group, which may characterize reduced metabolic reserves of cells. In neutrophilic granulocytes, there is a decrease in G6PDG, an enzyme that triggers glycolysis along the pentose phosphate pathway and contributes to the reduction of nicotinamide adenine dinucleotide phosphate (NADP) to NADPH, which is necessary for the formation of reduced glutathione that binds oxidants. With its insufficiency, a decrease in the energy reserves of cells occurs. In neutrophilic blood granulocytes in children with erosive and ulcerative lesions of the stomach and duodenum with H. pylori infection, a decrease in metabolic reserves is observed, which is associated with inhibition of metabolic processes in cells.